United Nations Post-2015 Agenda for global development: perspectives from China and Europe - Thomas Fues; Jiang Ye (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
This collection of scholarly articles reflects the main findings of a dialogue and research programme between the Shanghai Institutes for International Studies (SIIS) and the German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE) on the United Nations post-2015 agenda for global development. The contributions demonstrate a surprising degree of convergence in German and Chinese analytical approaches but also point to areas of substantive disagreement. Scholars from both institutions emphasise the historic significance of the post-2015 agenda which aims at defining a universal paradigm of sustainable development, and they maintain that poverty eradication and the unfinished business of the Millennium Development Goals (MDGs) must stand at the centre of the new framework. Differences between the scholars relate to the meaning of national sovereignty and the relevance of political factors such as good governance, rule of law and human rights. Differing nuances on certain aspects notwithstanding, the contributions offer a wide range of valuable insights and policy recommendations in support of a closer cooperation between China and Europe in the post-2015 process.
Keywords: 330; Agenda 2030; Regionale + globale + transnationale Governance